INdependenT prEscribinG in community phaRmAcy; whaT works for whom, why and in what circumstancEs (INTEGRATE): Realist review study protocol [version 1; peer review: 2 approved] - Andrew Sturrock; Tony Kelly; Vivienne Hibberd; Ian Maidment; Ola Amr Abdelfatah; Nia Roberts; Ellen Schafheutle; Andrea Hilton; Keith Holden; Geof Wong; Nick Haddington; Lesley Scott (NIHR Open Research)
Introduction The last decades have witnessed a series of initiatives in the United Kingdom (UK) to enhance patient access to quality care including access to medicine without compromising patient’s safety. Pharmacist independent prescribing is one of the initiatives introduced in 2006 with the intention of making more effective use of the skills and competencies of health professionals. Community pharmacy has a key role in the NHS long-term plan since pharmacies offer convenient and accessible sources of healthcare advice for the public. This role is more evident with the introduction of prescribing for all qualified pharmacists at the point of registration starting 2026. This realist review aims to explore how does independent prescribing in community pharmacy works, for whom, in what circumstances and how. Method and analysis Realist research seeks to explore and explain complex social interventions by utilising programme theories providing causal explanations of outcomes in terms of context-mechanism-outcome configurations. INTEGRATE will progress through six stages. In the first stage, we will partner with Patient, Public, Involvement and Engagement Group (PPIE) and Practitioner Stakeholder Group (SG), to further scrutinise the review’s focus. In stage 2, we will develop initial programme theories for what makes independent prescribing effective in community pharmacy, for whom, in what circumstances and how. In the third stage, we will conduct literature searches to gather secondary data that will help refine our initial programme theories. In stage 4, we will select and appraise identified articles by screening titles, abstracts and full texts against inclusion and exclusion criteria. In stage 5, we will extract, document and code relevant data, followed by realist analysis with contributions from the PPIE and SG. Stage 6 focuses on refining programme theories and identifying key mechanisms that lead to desired outcomes. PROSPERO registration: CRD42023468451